2023
DOI: 10.1109/access.2023.3255781
|View full text |Cite
|
Sign up to set email alerts
|

Task Scheduling in Cloud Computing: A Priority-Based Heuristic Approach

Abstract: In this paper, a task scheduling problem for a cloud computing environment is formulated by using the M/M/n queuing model. A priority assignment algorithm is designed to employ a new data structure named the waiting time matrix to assign priority to individual tasks upon arrival. In addition to this, the waiting queue implements a unique concept based on the principle of the Fibonacci heap for extracting the task with the highest priority. This work introduces a parallel algorithm for task scheduling in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Study in Ref. 37 presents a parallel algorithm for task scheduling, where both the priority assignment to tasks and the construction of the heap are concurrently executed. Authors in Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Study in Ref. 37 presents a parallel algorithm for task scheduling, where both the priority assignment to tasks and the construction of the heap are concurrently executed. Authors in Ref.…”
Section: Related Workmentioning
confidence: 99%
“…A Need Based lining model was produced for task booking in [11]. In any case, the planned model has not been applied in a powerful distributed computing climate.…”
Section: Related Workmentioning
confidence: 99%
“…This section, focus on SI algorithms. The study revealed that SI algorithms were used to solve several optimization issues, like cloud scheduling [43,44].The following are the primary causes:  Environments for cloud computing are distributed and dynamic. Because the SI algorithms are distributed and decentralized, they can be used to solve real-time cloud scheduling issues.…”
Section: Literature Reviewmentioning
confidence: 99%